2017
DOI: 10.1038/s41598-017-04619-3
|View full text |Cite
|
Sign up to set email alerts
|

Belowground top-down and aboveground bottom-up effects structure multitrophic community relationships in a biodiverse forest

Abstract: Ecosystem functioning and human well-being critically depend on numerous species interactions above- and belowground. However, unraveling the structure of multitrophic interaction webs at the ecosystem level is challenging for biodiverse ecosystems. Attempts to identify major relationships between trophic levels usually rely on simplified proxies, such as species diversity. Here, we propose to consider the full information on species composition across trophic levels, using Procrustes correlation and structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 66 publications
4
37
0
Order By: Relevance
“…However, other studies have indicated that tree species of initial ecological sequences have a greater presence of AMF species in relation to the climax (late) sequences, especially when mycotrophic forest species are present (Zangaro et al, 2000;Uibopuu et al, 2009). In fact, microbial symbionts (AMF) have positive and important effects on plant communities (Schuldt et al, 2017).…”
Section: Forestry Successionsmentioning
confidence: 99%
“…However, other studies have indicated that tree species of initial ecological sequences have a greater presence of AMF species in relation to the climax (late) sequences, especially when mycotrophic forest species are present (Zangaro et al, 2000;Uibopuu et al, 2009). In fact, microbial symbionts (AMF) have positive and important effects on plant communities (Schuldt et al, 2017).…”
Section: Forestry Successionsmentioning
confidence: 99%
“…It is generally accepted that soil microbial community is controlled by the bottom-up force [38,39]. Normally, understory vegetation is considered as a minor portion of biomass in a forest ecosystem and contributes less to the bottom-up force on soil decomposers than overstory plants.…”
Section: The Impacts Of Understory Removal On Soil Microbial Communitymentioning
confidence: 99%
“…We used data on 24 organism groups originally compiled by Schuldt et al (2015) (see also Schuldt et al 2017). The data include producers (plants), consumers (arthropods) and microorganisms (Table 1), and were classified according to their ecology into six trophic guilds (Supplementary material Appendix 1).…”
Section: Species Sampling and Trophic Guildsmentioning
confidence: 99%